옥수수 부산물을 이용한 주름 개선 기능성 소재 활용 가능성 연구 - 김혜진; Hye Jin Kim; 최우석; Woo Seok Choi; 이준섭; June Seob Lee; 김자영; Ja Young Kim; 김무한; Moo-han Kim; 이창현; Chang Hyeon Lee (大韓化粧品學會誌, 2023)
본 연구에서는 활용되지 못하고 폐기 되는 옥수수 부산물을 이용하여 주름 개선 기능성 소재로의 활용 가능성을 탐색하는 것을 목적으로, 초당 및 찰옥수수 10 개 품종에 대해 부위별 유효성분 탐색 및 정량분석을 통하여 업사이클링(upcycling) 소재로의 활용성을 제시하고자 하였다. 초당 및 대학찰옥수수의 부위별(알곡, 속대, 포엽, 수염) 추출물의 콜라겐 생성량 측정으로 주름 개선 효능평가 결과, 속대가 100 μg/mL의 농도에서 각각 176.5, 140.0%로 우수한 활성을 나타내었다. 속대에서 LC-MS/MS 정성분석으로 18 개 성분이 검색되었으며, 이 중 N, N'-diferuloylputrescine (DFP)을 유효성분으로 하여 품종 및 부위별 정량분석을 하였다. 그 결과, 속대 및 알곡에서만 DFP가 확인되었으며, 속대에서는 초당옥수수의 골드슈가(39.6 μg/g), 찰옥수수의 대학찰(38.4 μg/g) 품종에서 가장 높게 검출되었다. 속대는 알곡을 탈립 후 남은 부산물로써 콜라겐 생성 촉진 소재로서 부가가치를 새롭게 창출할 수 있을 것으로 기대되며, 본 연구를 통해 버려지는 속대의 주름 개선 기능성 소재로의 활용 가능성을 제시하고자 한다. In this study, to explore the possibility of using discarded by-products of corn as a wrinkle-improving functional material, the active ingredient contained in each part including kernel, cob, husk, and silk of 10 varieties of chodang and waxy corn was identified and the content was analyzed to suggest the possibility of corn by-products as upcycling materials. As a result of evaluating the collagen synthesis efficacy of extracts by part, the cob in chodang and waxy corns showed significant activity at 100 μg/mL concentration of 176.5 and 140.0%, respectively. The LC-MS/MS qualitative analysis resulted in the identification of 18 components in the cob, of which N, N'-diferuloylputrescine (DFP) was selected as an active ingredient, and the quantitative analysis was conducted by variety and part. As a result, DFP was confirmed only in the cob and kernel, and it was most frequently detected in the cob of the Goldsugar of chodang corn (39.6 μg/g) and Daehakchal of waxy corn (38.4 μg/g). The c ob i s a b y-product left over from grain removal, and is expected to create new added value as a material that promotes collagen synthesis. Through this study, we propose the possibility of using discarded cob as a wrinkle-improving functional material.